3D porous graphene with ultrahigh surface area for microscale capacitive deionization. (January 2015) - Li, Zhuo; Song, Bo; Wu, Zhenkun; Lin, Ziyin; Yao, Yagang; Moon, Kyoung-Sik; Wong, C.P.
Abstract: Capacitive deionization (CDI) is an emerging technology to supply deionized water as liquid coolant for the thermal management in microelectronics. Graphene has been demonstrated as a promising candidate for CDI electrode. However, the performance of current graphene-based CDI is far below expectation due to the limited specific surface area (SSA) and electrical conductivity of the chemically reduced graphene. Here we presented a KOH-activated graphene that has ultrahigh SSA of 3513 m 2 /g and electrical conductivity of 104 S/m. With improved materials properties, an ultrahigh electrosorption capacity of 11.86 mg/g and a significant adsorption rate of 20 min are achieved. Graphical abstract: Highlights: Capacitive deionization (CDI) is an emerging technology to supply deionized water as liquid coolant for the thermal management in microelectronics. KOH-activated graphene has an ultrahigh specific surface area of 3513 m 2 /g and electrical conductivity of 104 S/m. KOH-activated graphene-based CDI can achieve an electrosorption capacity of 11.86 mg/g, which is the highest value among graphene-based electrode reported for CDI applications at the same conditions.